Deviations Against Awig-Awig As Written Customary Law In Balinese Communities - Purwanto, Aldira Mara Ditta Caesar; Yulianingsih, Wiwin; Waluyo (VJJ, 2020)
The application of awig-awig as written customary law which is still used and obeyed by the Balinese people, of course this does not rule out the possibility of deviation. Deviations or violations committed by the Balinese people are generally resolved according to the rules written in awig-awig. The research methodology carried out in this study begins with the identification of a variety of literature related to customary law in terms of problems that occur and challenges that must be faced by the community. Then arranged to come up with the right problem formulation which later can be comprehensively reviewed through field studies and direct observations especially related to the problem taken in this research namely the deviation from the application of awig-awig as written customary law. The results obtained in this study aim to determine the deviations that occur in the Balinese community and how the Balinese community to resolve them.